Immediate Effects of Manual Muscle Stretching on Respiratory Capacity, Heart Rate Variability, and Diaphragmatic Function in Patients With COPD - Hsin-Lun Yang; Jian-Cheng Peng; Yu-Ting Huang; Hui-Ching Cheng; Ching-Hsia Hung; Chiung-Zuei Chen; Sheng-Yuan Wang; Chin-Wei Kuo; Kun-Ling Tsai (Annals of Rehabilitation Medicine, 2026)
Objective: To investigate the acute physiological responses following a single session of manual muscle stretching in patients with moderate to severe chronic obstructive pulmonary disease (COPD).Methods: A single-group pre–post design was used. Nineteen participants with moderate to severe COPD received one session of manual stretching, incorporating passive stretching and muscle energy techniques targeting the anterior scalene, upper trapezius, pectoralis, and diaphragm muscles. Primary outcomes included spirometry values, static lung volumes, heart rate variability (HRV), and diaphragmatic ultrasound. Secondary outcomes included respiratory muscle strength, upper limb flexibility, and symptom scores.Results: Following the intervention, participants exhibited a significant increase in expiratory reserve volume and diaphragmatic mobility, accompanied by a decrease in resting heart rate. HRV parameters (SDNN, RMSSD, LF, HF, and TP) showed significant changes following the intervention. Maximal inspiratory pressure increased from 76±47% to 85±51%, and maximal expiratory pressure increased from 55±30% to 67±34%, along with enhanced upper limb flexibility. Chest tightness, as assessed by the COPD Assessment Test, was significantly reduced. However, no significant changes were observed in spirometry values (FEV1, FVC, FEV1/FVC), other static lung volumes (TV, IRV, IC, VC), standardized HRV indices (HFnu, LFnu, LF/HF), or modified Medical Research Council scores.Conclusion: A single session of manual muscle stretching may be associated with immediate changes in respiratory mechanics, autonomic function, and symptom perception in patients with COPD.